2019
DOI: 10.1021/acsami.9b08146
|View full text |Cite
|
Sign up to set email alerts
|

In Situ TEM Study of the Amorphous-to-Crystalline Transition during Dielectric Breakdown in TiO2 Film

Abstract: Dielectric breakdown of oxides is a main limiting factor for improvement of the performance of electronic devices. Present understanding suggests that defects produced by intense voltage accumulate in the oxide to form a percolation path connecting the two electrodes and trigger the dielectric breakdown. However, reports on directly visualizing the process at nanoscale are very limited. Here, we apply in situ transmission electron microscopy to characterize the structural and compositional changes of amorphous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…During the process, the upper part of the nanocrystal (next to the Si anode) remains crystalline. A similar structurecrystalline at anode and amorphous at cathodewas observed in the crystallization of the amorphous TiO 2 film in our previous work …”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…During the process, the upper part of the nanocrystal (next to the Si anode) remains crystalline. A similar structurecrystalline at anode and amorphous at cathodewas observed in the crystallization of the amorphous TiO 2 film in our previous work …”
Section: Resultssupporting
confidence: 85%
“…A similar structurecrystalline at anode and amorphous at cathodewas observed in the crystallization of the amorphous TiO 2 film in our previous work. 19 The recorded electric current shows relatively steady increases in the first 30 s and some spikes in the third application of bias (Figure 3b), presumably resulting from the buildup of charged point defects under intense field and the subsequent formation of temporary percolation pathways across the nanocrystal. 4,11 The large current density causes local resistive heating of the nanocrystal when the bias is on and fast quenching when the bias is off, which is responsible for the changes in the nanocrystal contour.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The efforts to engineer novel interface structures are often hindered by difficulties reconciling the properties of ultrathin films at macroscopic and microscopic scales. The CoFeB/MgO interface forms the basis of magnetic tunnel junction (MTJ) technology due to its tunneling magnetoresistance (TMR) and perpendicular magnetic anisotropy (PMA). Subjecting the thin MgO tunnel barrier in MTJs to repeated electrical stress induces breakdown, which limits the endurance of magnetoresistive random-access memory (MRAM) devices. This situation is similar to the time-dependent dielectric breakdown (TDDB) in complementary metal-oxide–semiconductor (CMOS) gate oxides. Researchers have reported that the breakdown can be delayed by inserting an ultrathin film of metallic Mg into the CoFeB/MgO interface during MgO barrier formation to prevent CoFeB oxidization. Mg termination has also been shown to suppress the magnetic dead layer in ferromagnetic electrodes. …”
Section: Introductionmentioning
confidence: 81%
“…In situ TEM techniques using a specimen holder equipped with various capabilities enable the direct characterization of structure and physical properties of materials simultaneously. To study the dielectric breakdown in copper oxides, we coated copper oxides on a wedge shape Si substrate and loaded the substrate on a Hysitron PI95 STEM specimen holder which we have successfully used to study the effects of applied voltages on different oxides [10], [11]. Different parts of the copper oxide coating were selectively studied by placing a W probe in contact with the region of interest.…”
Section: Introductionmentioning
confidence: 99%